'God's most beautiful name is peace': Rabbi Menachem Froman's vision of inter-religious peace between Israelis and Palestinians. Issue 3 (4th May 2021) - Shemer, Nesya
ABSTRACT: Rabbi Menachem Froman was a foremost religious peace activist who sought to promote Israeli-Palestinian reconciliation through conversations with religious leaders of the two peoples and discussions with politicians in Israel and the world. This article examines his vision of inter-religious peace and his attempts to realise this vision, using archival materials revealed after his death in 2013 as well as his previously published philosophical musings and writings.